Preparation method of in-situ polymerization semi-solid battery and battery thereof

By using polymer precursor liquid to inject dry cell and heat polymerization in in-situ polymerization semi-solid battery cells, the limitations of electrode interface uniformity and polymerization effect are solved, and the circulation performance and stability of the battery are improved.

CN119905674APending Publication Date: 2025-04-29JIANGXI GANFENG BATTERY TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510108103.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The performance of existing in-situ polymerized semi-solid state batteries is limited by electrode interface uniformity and polymerization effect, resulting in unstable circulation performance.

Method used

By mixing polymer monomers, crosslinking agents, initiators, lithium salts and functional additives, they are prepared into an in-situ cured polymer precursor, injected into a dry cell and left to stand, and then heated in an oven to form a semi-solid battery. This method improves contact tightness and polymerization uniformity between the electrode and the electrolyte interface.

Benefits of technology

It improves the circulation performance and stability of solid-state batteries, reduces the interface impedance, simplifies the electrolyte curing process, and enhances the compatibility between the electrode and the electrolyte interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905674A_ABST
    Figure CN119905674A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an in-situ polymerization semi-solid battery. The preparation method comprises the following steps: S1, mixing a positive active material, a conductive agent, a binder and a lithium salt to prepare positive slurry, and coating an aluminum foil with the positive slurry to prepare a positive plate; s2, mixing a negative active material, a conductive agent, a binder and a lithium salt to prepare negative slurry, and coating a copper foil with the negative slurry to prepare a negative plate; s3, coating a diaphragm with a lithium salt to prepare a mixed diaphragm; s4, preparing the prepared positive plate, the prepared negative plate and the prepared mixed diaphragm into a dry battery cell through an assembly process; s5, stirring and mixing a polymer monomer, a cross-linking agent, an initiator, an organic solvent, a lithium salt and a functional additive to prepare an in-situ curing polymer precursor solution; and S6, injecting the in-situ curing polymer precursor solution into the dry battery cell, standing for 6-72 hours, and then putting the dry battery cell into a drying oven for polymerization to obtain the semi-solid battery. According to the preparation method of the semi-solid-state battery, the interface uniformity of the in-situ solid-state electrode is improved, and the cycle performance of the solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular, relates to a method for preparing an in-situ polymerized semi-solid battery and a battery thereof. Background Art

[0002] Solid polymer electrolytes (SPEs) have outstanding advantages such as low flammability, low electrolyte leakage, safety, high flexibility and interface stability. They are considered to be an effective way to solve the safety performance problems of existing lithium-ion batteries from the source. Traditional solid polymer electrolytes are usually prepared separately and then assembled into batteries. The solid electrolytes prepared by this non-in-situ process have poor interface compatibility and low ionic conductivity due to their loose contact with the electrode surface, and the prepared electrolyte membrane is thick and difficult to achieve high energy density. In addition, this method is incompatible with existing liquid battery production lines, which greatly increases costs and limits the commercial development of solid-state batteries.

[0003] The in-situ curing method uses the precursor solution as the electrolyte in the liquid battery, assembles the battery according to the assembly method of the liquid battery, and after the battery is encapsulated, the precursor solution is polymerized under specific conditions to obtain a polymer electrolyte. Compared with the non-in-situ method, the advantages of the in-situ method are that the liquid precursor can infiltrate the positive electrode pores, which is conducive to building a good electrode / electrolyte contact interface and better ion conduction in the positive electrode. In addition, this method is compatible with the existing liquid battery manufacturing process system and has good application prospects.

[0004] In-situ solidification of solid electrolytes is to mix monomers or oligomers, initiators, and liquid electrolytes to form polymer precursors, and in-situ initiate polymerization of monomer molecules under certain external conditions (such as thermal initiation, photoinitiation, etc.) to obtain polymer electrolytes that can conduct lithium ions. Since ultraviolet light and other light cannot penetrate shells such as aluminum-plastic films, photoinitiation cannot be applied to in-situ polymerization at the cell level, so thermal initiation is the most suitable polymerization method. Thermal initiation mainly heats the battery for polymerization by heat conduction. The outside of the cell heats up first, and then the heat is conducted to the inside of the cell, resulting in uneven distribution of the thermal field inside and outside the cell, which makes thermal initiation prone to uneven curing.

[0005] The Chinese invention application with publication number CN108493486A uses acrylate and initiator dissolved in electrolyte, injected into the battery, and under heating conditions, initiates the polymerization of unsaturated double bonds to form an integrated gel polymer battery; the Chinese invention application with publication number CN111533851A uses a mixture of small molecule carbonate containing double bonds, ethylene glycol acrylate, and initiator, injected into the interface of the solid-state battery, and thermally initiates polymerization to form an electrode-electrolyte integrated all-solid-state battery. The above methods directly inject one or more monomer precursor solutions into the battery cell, and initiate monomer polymerization by heating and curing. However, due to the uneven distribution of the thermal field inside the battery cell and the different local microenvironments, it is difficult to maintain uniform polymerization of the monomers, resulting in local overcharge or over-discharge of the battery cell, affecting the overall performance of the solid-state battery cell. Summary of the invention

[0006] In order to improve the performance of the existing in-situ polymerization semi-solid battery, the present invention provides a method for preparing an in-situ polymerization semi-solid battery, comprising the following steps:

[0007] S1: Mixing positive electrode active material, conductive agent, binder and lithium salt to prepare positive electrode slurry and coating it on aluminum foil to prepare positive electrode sheet; S2: Mixing negative electrode active material, conductive agent, binder and lithium salt to prepare negative electrode slurry and coating it on copper foil to prepare negative electrode sheet; S3: Coating lithium salt on diaphragm to prepare mixed diaphragm; S4: Assembling the prepared positive electrode sheet, negative electrode sheet and mixed diaphragm to prepare dry battery cell; S5: Mixing polymer monomer, cross-linking agent, initiator, organic solvent, lithium salt and functional additive to prepare in-situ curing polymer precursor solution; S6: Injecting the in-situ curing polymer precursor solution into the dry battery cell and letting it stand for 6h to 72h; S7: Placing the battery cell after standing in step S6 in an oven for polymerization to obtain a semi-solid battery.

[0008] Furthermore, in the positive electrode slurry in the step S1, the mass ratio of the positive electrode active material, the conductive agent, the binder, and the lithium salt is 95:1.5:1.5:2.

[0009] Furthermore, the positive electrode active material in step S1 is a composite material comprising one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium vanadium phosphate, and the like.

[0010] Furthermore, the negative electrode active material in step S2 is one or more composites of carbon-containing materials, silicon materials, silicon-carbon composite materials, silicon-oxygen compound materials, etc.

[0011] Furthermore, the in-situ curing polymer precursor solution in step S5 is prepared with the following mass percentages: 1-20% of polymerizable monomer, 1-10% of cross-linking agent, 0.1-1% of initiator, 10-20% of lithium salt, and 5%-10% of the functional additive.

[0012] Furthermore, after the in-situ curing polymer precursor solution is injected into the dry battery cell in step S6, the dry battery cell is subjected to heat insulation treatment using heat insulation cotton.

[0013] Furthermore, the initiator in step S5 comprises one or more of an azo initiator, a peroxide initiator, an amine catalyst initiator and an organophosphorus initiator.

[0014] Furthermore, the cross-linking agent in step S5 comprises one or more of pentaerythritol tetraacrylate (PETEA), polyethylene glycol diacrylate (PEGDA), and tetraethylene glycol dimethacrylate.

[0015] Furthermore, the in-situ polymerizable monomers of S4 include one or more of monomers containing unsaturated carbon-carbon double bonds, cyclic monomers capable of ring-opening polymerization, and monomers containing polymerizable active functional groups.

[0016] On the other hand, the present invention also provides a semi-solid-state battery prepared by any of the methods for preparing an in-situ polymerization semi-solid-state battery.

[0017] The preparation method of the semi-solid-state battery of the present invention improves the uniformity of the in-situ solid-state electrode interface, improves the interface compatibility, and thus improves the cycle performance of the solid-state battery; at the same time, it simplifies the electrolyte curing process, improves the polymerization effect of in-situ curing, makes the electrode and electrolyte interface tighter, reduces the interface impedance, and improves the cycle stability of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a diagram of the polymerization state of the battery of Comparative Example 1 after heating;

[0020] Figure 2 This is a diagram of the polymerization state of the battery after heating according to Example 1 of the present invention;

[0021] Figure 3 It is a comparison chart of the cycle performance test results of Example 1 of the present invention and Comparative Example 1;

[0022] Figure 4 It is a comparison chart of the cycle performance test results of Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] This embodiment provides a method for preparing an in-situ polymerization semi-solid battery, comprising the following steps:

[0025] S1: Mixing the positive electrode active material, the conductive agent, the binder and the lithium salt in proportion to prepare a positive electrode slurry and coating it on an aluminum foil to prepare a positive electrode sheet;

[0026] S2: Mixing the negative electrode active material, the conductive agent, the binder and the lithium salt in proportion to prepare a negative electrode slurry and coating the mixture on a copper foil to prepare a negative electrode sheet;

[0027] S3: coating a lithium salt on a separator to prepare a hybrid separator;

[0028] S4: The positive electrode sheet prepared in step S1, the negative electrode sheet prepared in step S2, and the separator prepared in step S3 are assembled to prepare a dry battery cell;

[0029] S5: mixing the polymer monomer, the cross-linking agent, the initiator, the organic solvent, the lithium salt and the functional additive to prepare an in-situ curing polymer precursor solution;

[0030] S6: injecting the in-situ curing polymer precursor solution into the dry battery cell and leaving it to stand for 6 hours to 72 hours;

[0031] S7: placing the battery cell after standing in step S6 in an oven for polymerization to obtain a semi-solid battery.

[0032] Furthermore, the lithium salt described in step S1 or S2 is one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSi).

[0033] Further, the polymer monomer in step S5 includes one or more of a monomer containing an unsaturated carbon-carbon double bond, a ring-opening polymerizable cyclic monomer, and a monomer containing a polymerizable active functional group. For example, it can be vinylene carbonate, vinyl ethylene carbonate, dimethyl allyl malonate, diethyl allyl malonate, vinyl acetate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, dimethyl allyl diformate, diethyl allyl malonate, methallyl carbonate, methyl vinyl sulfone, ethyl vinyl sulfone, vinyl acetate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, acrylamide, N,N methylenebisacrylamide, N-methylmaleamide, etc.; polyethylene oxide, polypropylene oxide, polyepichlorohydrin and its copolymer, polytetrahydrofuran, etc.

[0034] Furthermore, the cross-linking agent in step S4 comprises one or more of pentaerythritol tetraacrylate (PETEA), polyethylene glycol diacrylate (PEGDA), and tetraethylene glycol dimethacrylate (TEGDMA).

[0035] Furthermore, the initiator in step S4 comprises one or more of an azo initiator, a peroxide initiator, an amine catalyst initiator and an organophosphorus initiator: for example, it may be one or more of azobisisobutyronitrile (AI BN), azobisisoheptanenitrile, benzoyl (BPO), diisopropylbenzene peroxide, dibenzoyl peroxide and ammonium persulfide.

[0036] Furthermore, the organic solvent in step S4 is one or more of ethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0037] Furthermore, the lithium salt in step S4 is one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium trifluoromethylsulfonate (LiCP3SO3), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), and lithium difluorobis(oxalatophosphate) (LiDFBP).

[0038] Furthermore, the in-situ solidified electrolyte precursor described in step S4 is prepared according to the following mass percentages: 1-20% of polymerized monomer, 1-10% of cross-linking agent, 0.1-1% of initiator, 10-20% of lithium salt, 5%-10% of functional additives, and the rest is organic solvent. Furthermore, the battery cell described in step S4 is obtained by winding or laminating a positive electrode sheet, a negative electrode sheet, and a separator placed between the positive electrode sheet and the negative electrode sheet.

[0039] Furthermore, the positive electrode active material in step S1 is a composite material comprising one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium vanadium phosphate, etc.

[0040] Furthermore, the negative electrode active material in step S1 is one or more composites including metallic lithium, lithium alloy, carbon material, silicon material, silicon-carbon composite material, silicon-oxygen compound material, etc.

[0041] Furthermore, the standing time of the in-situ curing polymer precursor solution in step S6 is 6 hours to 72 hours, preferably 24 hours, so that the polymer precursor solution can fully infiltrate the pores of the positive and negative electrode sheets.

[0042] Furthermore, after the in-situ curing polymer precursor solution is injected into the dry battery cell in step S6, the dry battery cell is insulated with thermal insulation cotton and then left to stand for 6 hours to 72 hours to prevent the heat generated by the dissolution of the lithium salt from being lost to the outside of the battery cell shell.

[0043] Furthermore, in step S7, the polymerization temperature of the battery in the oven can be set to 45° C. to 85° C., preferably to 80° C., and the polymerization time of the polymer precursor solution in the oven is 6 h to 36 h.

[0044] Furthermore, the diaphragm in step S3 is a PE composite diaphragm with a double-sided ceramic layer, the ceramic coating is a mixture of AL2O3 and lithium salt, the base film thickness is 7 μm, and the ceramic coating thickness is 2 μm.

[0045] The outstanding features and significant improvements of the present invention will be further illustrated below through examples and embodiments, which are intended only to illustrate the present invention and not to limit the present invention.

[0046] Example 1

[0047] S1: Mix the positive electrode active material lithium nickel cobalt manganese oxide (NCM811), conductive carbon black, PVDF, and LiPF6 in a mass ratio of 95:1.5:1.5:2. After mixing, add N-methylpyrrolidone (NMP), stir and mix thoroughly to obtain a positive electrode slurry, evenly coat it on aluminum foil, dry it, and then roll and die-cut it to obtain a positive electrode sheet.

[0048] S2: Mix silicon-carbon negative electrode, conductive carbon, carbon nanotubes, binder (CMC), binder (SBR), binder (PAA), and LiPF6 in a mass ratio of 94.85:0.5:0.15:0.25:0.5:2.75:1, add deionized water after mixing, stir and mix thoroughly to obtain negative electrode slurry, apply the negative electrode slurry to copper foil, dry and roll to obtain negative electrode sheet. S3: Add lithium salt to Al2O3 to prepare diaphragm coating slurry, apply the prepared slurry on both sides of the diaphragm, and prepare a double-sided ceramic layer PE composite diaphragm after drying. The size of the prepared diaphragm is (2μm aluminum oxide layer + 7μm base film + 2μm aluminum oxide layer).

[0049] S4: The NCM811 positive electrode sheet, the silicon-carbon negative electrode sheet, and the diaphragm are assembled in sequence through lamination, tab welding, and top and side sealing to obtain a dry battery to be filled with liquid.

[0050] S5: Preparation of in-situ curing polymer precursor: PC, EMC, DEC, FEC, LiPF6, LiPO2F2, and DTD are fully stirred and dissolved in a mass ratio of 15:35:25:8:15:1:1 to obtain a liquid base liquid, and then monomer vinyl carbonate, cross-linking agent pentaerythritol tetraacrylate, and azobisisobutyronitrile are added to the base liquid and mixed evenly to obtain an in-situ curing polymer precursor, wherein the mass ratio of the liquid base liquid, vinyl carbonate, pentaerythritol tetraacrylate, and azobisisobutyronitrile is 94.9:3:2:0.1.

[0051] S6: Inject the electrolyte prepared in step S5 into the battery to be filled, and let it stand at room temperature for 24 hours.

[0052] S7: Place the rested battery cell in an oven at 80°C and bake for 12 hours to polymerize the polymer precursor liquid to form a semi-solid battery.

[0053] S8: The semi-solid-state battery is formed at 45°C and aged for 24 hours, and finally sealed and divided at room temperature.

[0054] S9: The battery after being divided into different capacities is disassembled, and the battery interface is observed as shown in the figure; at the same time, the battery after being divided into different capacities is subjected to a cycle performance test.

[0055] Comparative Example 1

[0056] S1: Mix the positive electrode active material lithium nickel cobalt manganese oxide (NCM811), conductive carbon black and PVDF in a mass ratio of 96.5:1.5:2. After mixing, add N-methylpyrrolidone (NMP), stir and mix thoroughly to obtain positive electrode slurry, evenly coat it on aluminum foil, dry it, and then roll and die-cut it to obtain a positive electrode sheet.

[0057] S2: Mix silicon-carbon negative electrode, conductive carbon, carbon nanotubes, binder (CMC), binder (SBR), PAA in a mass ratio of 94.85:0.5:0.15:0.25:0.5:3.75, add deionized water after mixing, stir and mix thoroughly to obtain negative electrode slurry, coat the negative electrode slurry on copper foil, dry and roll cut to obtain negative electrode sheet.

[0058] S3: Add lithium salt to Al2O3 to prepare a diaphragm coating slurry, apply the prepared slurry on both sides of the diaphragm, and prepare a double-sided ceramic layer PE composite diaphragm after drying. The size of the prepared diaphragm is (2μm aluminum oxide layer + 7μm base film + 2μm aluminum oxide layer).

[0059] S4: The NCM811 positive electrode sheet, the silicon-carbon negative electrode sheet, and the diaphragm are assembled in sequence through lamination, tab welding, and top and side sealing to obtain a dry battery to be filled with liquid.

[0060] S5: Prepare in-situ curing polymer precursor: fully stir and dissolve PC, EMC, DEC, FEC, LiPF6, LiPO2F2 and DTD in a mass ratio of 15:35:25:8:15:1:1 to obtain a liquid base liquid, and then add monomer vinylene carbonate, cross-linking agent pentaerythritol tetraacrylate and azobisisobutyronitrile to the base liquid and mix evenly to obtain an in-situ curing polymer precursor, wherein the mass ratio of the liquid base liquid, vinylene carbonate, pentaerythritol tetraacrylate and azobisisobutyronitrile is 94.9:3:2:0.1.

[0061] S6: Inject the electrolyte prepared in step S5 into the battery to be filled, and let it stand at room temperature for 24 hours.

[0062] S7: Place the rested battery cell in an oven at 80°C and bake for 12 hours to polymerize the polymer precursor liquid to form a semi-solid battery.

[0063] S8: The semi-solid-state battery is formed at 45°C and aged for 24 hours, and finally sealed and divided at room temperature.

[0064] S9: The battery after being divided into different capacities is disassembled, and the battery interface is observed as shown in the figure; at the same time, the battery after being divided into different capacities is subjected to a cycle performance test.

[0065] Example 2

[0066] S1: Mix the positive electrode active material lithium nickel cobalt manganese oxide (NCM811), conductive carbon black, PVDF, and LiPF6 in a mass ratio of 95:1.5:1.5:2. After mixing, add N-methylpyrrolidone (NMP), stir and mix thoroughly to obtain a positive electrode slurry, evenly coat it on aluminum foil, dry it, and then roll and die-cut it to obtain a positive electrode sheet.

[0067] S2: Mix the silicon-carbon negative electrode, conductive carbon, carbon nanotubes, binder (CMC), binder (SBR), PAA, and LiPF6 in a mass ratio of 94.85:0.5:0.15:0.25:0.5:2.75:1, add deionized water after mixing, stir and mix thoroughly to obtain a negative electrode slurry, apply the negative electrode slurry to copper foil, dry, roll and cut to obtain a negative electrode sheet;

[0068] S3: Add lithium salt to Al2O3 to prepare a diaphragm coating slurry, apply the prepared slurry on both sides of the diaphragm, and prepare a double-sided ceramic layer PE composite diaphragm after drying. The size of the prepared diaphragm is (2μm aluminum oxide layer + 7μm base film + 2μm aluminum oxide layer).

[0069] S4: The NCM811 positive electrode sheet, the silicon-carbon negative electrode sheet, and the diaphragm are assembled in sequence through lamination, tab welding, and top and side sealing to obtain a dry battery to be filled with liquid.

[0070] S5: Prepare in-situ curing polymer precursor solution: fully stir and dissolve PC, EMC, DEC, FEC, LiPF6, LiPO2F2 and DTD in a mass ratio of 15:35:25:8:15:1:1 to obtain a liquid base solution, and then add monomer methyl methacrylate, cross-linking agent pentaerythritol tetraacrylate and azobisisobutyronitrile to the base solution and mix evenly to obtain an in-situ curing polymer precursor solution, wherein the mass ratio of liquid base solution, vinylene carbonate, pentaerythritol tetraacrylate and azobisisobutyronitrile is 94.9:3:2:0.1.

[0071] S6: Inject the electrolyte prepared in step S5 into the battery to be filled, and let it stand at room temperature for 24 hours.

[0072] S7: Place the rested battery cell in an oven at 80°C and bake for 12 hours to polymerize the polymer precursor liquid to form a semi-solid battery.

[0073] S8: The semi-solid-state battery is formed at 45°C and aged for 24 hours. Finally, it is sealed and divided at room temperature.

[0074] S9: The battery after being divided into different capacities is disassembled, and the battery interface is observed as shown in the figure; at the same time, the battery after being divided into different capacities is subjected to a cycle performance test.

[0075] Comparative Example 2

[0076] S1: Mix the positive electrode active material, lithium nickel cobalt manganese oxide (NCM811), conductive carbon black, PVDF, and LiPF6 in a mass ratio of 95:1.5:1.5:2, add N-methylpyrrolidone (NMP) after mixing, stir and mix thoroughly to obtain a positive electrode slurry, evenly coat it on an aluminum foil, dry it, and roll and die-cut it to obtain a positive electrode sheet;

[0077] S2: Mix the silicon-carbon negative electrode, conductive carbon, carbon nanotubes, binder (CMC), binder (SBR), and PAA in a mass ratio of 94.85:0.5:0.15:0.25:0.5:3.75, add deionized water after mixing, stir and mix thoroughly to obtain a negative electrode slurry, apply the negative electrode slurry to copper foil, and roll and cut to obtain a negative electrode sheet.

[0078] S3: The prepared slurry is coated on both sides of the diaphragm, and after drying, a double-sided ceramic layer PE composite diaphragm is prepared. The size of the prepared diaphragm is (2 μm aluminum oxide layer + 7 μm base film + 2 μm aluminum oxide layer).

[0079] S4: The NCM811 positive electrode sheet, the silicon-carbon negative electrode sheet, and the diaphragm are assembled in sequence through lamination, tab welding, and top and side sealing to obtain a dry battery to be filled with liquid.

[0080] S5: Prepare in-situ curing polymer precursor solution: fully stir and dissolve PC, EMC, DEC, FEC, LiPF6, LiPO2F2 and DTD in a mass ratio of 15:35:25:8:15:1:1 to obtain a liquid base solution, and then add monomer methyl methacrylate, cross-linking agent pentaerythritol tetraacrylate and azobisisobutyronitrile to the base solution and mix evenly to obtain an in-situ curing polymer precursor solution, wherein the mass ratio of liquid base solution, vinylene carbonate, pentaerythritol tetraacrylate and azobisisobutyronitrile is 94.9:3:2:0.1.

[0081] S6: Inject the electrolyte prepared in step S5 into the battery to be filled, and let it stand at room temperature for 24 hours.

[0082] S7: Place the rested battery cell in an oven at 80°C and bake for 12 hours to polymerize the polymer precursor liquid to form a semi-solid battery.

[0083] S8: The semi-solid-state battery is formed at 45°C and aged for 24 hours, and finally sealed and divided at room temperature.

[0084] S9: The battery after being divided into different capacities is disassembled, and the battery interface is observed as shown in the figure; at the same time, the battery after being divided into different capacities is subjected to a cycle performance test.

[0085] By comparison Figure 1 and 2 It can be found that the battery prepared in Comparative Example 1 did not produce obvious gel on the surface of the bare cell after heating and curing for 12 hours, and the degree of polymerization was low. However, as Example 1 of the semi-solid battery preparation method of the present invention, obvious gel was produced on the surface of the bare cell, indicating that the degree of polymerization was higher, and a better gel layer could be formed on the battery separator, which is conducive to forming a more uniform and stable interface while improving the mechanical properties of the separator.

[0086] from Figure 3 and 4 It can be seen from the battery cycle performance test data that: compared with comparative examples 1 and 2, the batteries prepared in Example 1 and Example 2 using the semi-solid battery preparation method of the present invention show better cycle performance, which indicates that the in-situ curing process brought about by the semi-solid battery preparation method of the present invention to uniformly disperse the lithium salt in the electrode piece or on the surface of the diaphragm through slurry coating helps the battery electrode piece to obtain a closer contact interface, thereby effectively reducing the interface impedance and improving the electrochemical performance of the battery.

[0087] The present invention evenly disperses lithium salt in the pores of the pole piece or on the surface of the diaphragm coating by homogenous coating, then mixes the polymerization monomer, initiator, organic solvent and lithium salt to obtain a polymer precursor solution, and finally injects the solution into the battery cell by liquid injection to obtain an in-situ solid-state battery. Since the liquid precursor solution injected into the battery cell will slowly dissolve the lithium salt in the pores of the pole piece and the diaphragm coating, and release a large amount of heat on the surface of the pole piece, prepolymerization is preferentially carried out on the surface of the pole piece under the action of the initiator, and at the same time, during the heating and curing process, the lithium salt in the pole piece is continuously dissolved from the pores of the pole piece or the diaphragm coating, promoting polymerization to form a more closely contacted interface; during the curing process of introducing an external heat source, the lithium salt in the pole piece and the diaphragm coating is continuously dissolved from the surface, promoting polymerization to form a more closely contacted interface.

[0088] Therefore, the present invention solves the problems of uneven polymerization of the electrode surface in the traditional in-situ solidification method and the loose contact of the electrode surface after curing caused by volume shrinkage during the curing process. The preparation method of the semi-solid battery of the present invention improves the uniformity of the in-situ solid electrode interface, improves the interface compatibility, and thus improves the cycle performance of the solid-state battery; at the same time, it simplifies the electrolyte curing process, improves the polymerization effect of in-situ curing, makes the interface between the electrode and the electrolyte tighter, reduces the interface impedance, and improves the cycle stability of the solid-state battery.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an in-situ polymerization semi-solid battery, comprising the following steps: S1: Mixing a positive electrode active material, a conductive agent, a binder and a lithium salt to prepare a positive electrode slurry and coating the mixture on an aluminum foil to prepare a positive electrode sheet; S2: mixing the negative electrode active material, the conductive agent, the binder and the lithium salt to prepare a negative electrode slurry and coating the mixture on a copper foil to prepare a negative electrode sheet; S3: coating a lithium salt on a separator to prepare a hybrid separator; S4: preparing a dry battery cell by assembling the prepared positive electrode sheet, the negative electrode sheet, and the mixed separator through an assembly process; S5: mixing the polymer monomer, the cross-linking agent, the initiator, the organic solvent, the lithium salt and the functional additive to prepare an in-situ curing polymer precursor solution; S6: injecting the in-situ curing polymer precursor solution into the dry battery cell and leaving it to stand for 6 h to 72 h; S7: placing the battery cell after standing in step S6 in an oven for polymerization to obtain a semi-solid battery.

2. The method for preparing an in-situ polymerization semi-solid battery according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the conductive agent, the binder, and the lithium salt in the positive electrode slurry in step S1 is 95:1.5:1.5:

2.

3. The method for preparing an in-situ polymerization semi-solid battery according to claim 1, characterized in that: The positive electrode active material in step S1 is a composite material including one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium vanadium phosphate, and the like.

4. The method for preparing an in-situ polymerization semi-solid battery according to claim 1, characterized in that: The negative electrode active material in step S2 is one or more composites of carbon-containing materials, silicon materials, silicon-carbon composite materials, silicon-oxygen compound materials, etc.

5. The method for preparing an in-situ polymerized semi-solid battery according to claim 1, characterized in that: The in-situ curing polymer precursor solution in step S5 is prepared with the following mass percentages: 1-20% of polymerizable monomer, 1-10% of cross-linking agent, 0.1-1% of initiator, 10-20% of lithium salt, and 5-10% of the functional additive.

6. The method for preparing an in-situ polymerized semi-solid battery according to claim 1, characterized in that: After the in-situ curing polymer precursor solution is injected into the dry battery cell in the step S6, the dry battery cell is subjected to heat insulation treatment using heat insulation cotton.

7. The method for preparing an in-situ polymerization semi-solid battery according to claim 1, characterized in that: The initiator in step S5 includes one or more of an azo initiator, a peroxide initiator, an amine catalyst initiator and an organophosphorus initiator.

8. The method for preparing an in-situ polymerization semi-solid battery according to claim 1, characterized in that: The cross-linking agent in step S5 includes one or more of pentaerythritol tetraacrylate (PETEA), polyethylene glycol diacrylate (PEGDA), and tetraethylene glycol dimethacrylate.

9. The method for preparing an in-situ polymerization semi-solid battery according to claim 1, characterized in that The in-situ polymerizable monomers of S4 include one or more of monomers containing unsaturated carbon-carbon double bonds, cyclic monomers capable of ring-opening polymerization, and monomers containing polymerizable active functional groups.

10. A semi-solid battery, characterized in that: The battery is prepared by the method for preparing an in-situ polymerization semi-solid battery as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of in-situ polymerization solid-state battery

    CN108493486A

  • Preparation method of polymer electrolyte and application of polymer electrolyte in all-solid-state battery

    CN111533851A

  • In-situ polymerized organic-inorganic composite solid-state battery

    CN111933894A